Explanation of Market Opportunities and its Impact on Foreign Market Entry Strategies (Case Study: Afghan Clothing) - Modaber, Mohammad Amin; Hamidizadeh, Mohammad Reza; Habibi, Ali Reza; Nazari, Marzia (Journal of Social Sciences - Kabul University, 2025)
Market opportunities are greater in foreign markets than in domestic markets, which including product abundance, product family breath, product quality, customer service requirements, and product advertising. These are considering competitive advantages for the organizations. The aim of the research is to explain market opportunities on strategies for entering foreign markets (by reviewing afghan clothing). Therefore, the objective of the present research is applied and its data was collected with a quantitative field approach (distribution of questionnaires). According to the unlimited population size, in this research the size of the population was unlimited and its sample size was fixed. The sample consisted of 16% students, 10% university professors, and 74% industrial sector employees in Afghanistan. SPSS and SMART-PLS software were used to analyze the questionnaire data. The finding has shown, that the market opportunities using market intelligence and marketing intelligence have a positive impact on foreign market entry, and the impact of market opportunities on foreign market entry strategies is significant.